The short-run macroeconomic impact of foreign aid to small states: An agnostic time series analysis - Hansen, Henrik; Headey, Derek D. (International Food Policy Research Institute, 2009)
We herein investigate the short-run macroeconomic impact of aid in small developing countries (SDCs) by using a vector auto regression (VAR) model to study the impact of aid on net import (absorption) and domestic demand (spending). We focus on average country effects within two country sub-groups, and find substantial differences between ‘aid-dependent’ SDCs and other SDCs that are more dependent on natural resources, tourism or financial services. In aid-dependent SDCs, aid absorption more or less equals spending, although only half of the aid flow is absorbed and spent. In the non-aid-dependent group, aid does not seem to be absorbed or spent in any systematic fashion.